General Practices of International Arbitral Tribunals Vis-A-Vis the Jurisdictional Conundrum - Vyas, Prakhar; Pohane, Varad; Awasthi, Shivanshu (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Arbitration has been the most effective and preferred tool to solve the disputes amicably among the countries and has most success though not limited to while dealing with the problems of international boundaries both land and maritime in nature. Like any other method of dispute resolution it too has some shortcomings due to the tribunals not being able to establish their jurisdiction on these disputes or sometimes the part of it which render any award by the tribunal disputable thereby leaving a piece of the problem unresolved. The article attempts to identify these various issues which come into being and study the different outcomes and reasoning of the arbitral tribunals while denying or modifying their jurisdiction. The mentioned issues are being supported by the actual case laws detailing the stance and views of the members of the tribunal and their interpretation of the agreement which had led to the existence of the arbitral tribunal. Eventually the article would also draw specific attention to the commercial disputes between the countries and a private entity which are governed by the International Conventions and highlight practices on part of the parties which render a dispute outside the scope of the tribunals jurisdiction with a specific focus on ICSID Convention and its limitations which makes its very objective to be unattainable. The authors also try to provide suggestions as to what steps should be undertaken by the parties and the system to eradicate these shortcomings and lead to an award which could provide a capable solution to the dispute of the parties.
Keywords: Arbitartion; ICSID Convention; Treaty of Ghent; Rainbow warrior; Guinea Bissau; Channel islands